INSTITUTIONAL MECHANISMS TO IMPROVE THE FINANCIAL LITERACY OF YOUNG PEOPLE AND THE PROTECTION OF THE RIGHTS OF CONSUMERS - E. A. Tereshchenko (Гуманитарные и юридические исследования)
Improving financial literacy among the Russian population - the problem is relatively new, but very relevant. Mechanisms are needed through which to communicate the skills to protect their legal rights in disputes with financial institutions. The article presents an overview of methods of educational and informational events in the field of consumer protection in the environment of pupils and students.